Case Report: Next-Generation Sequencing-Based Detection in A Patient with Three Synchronous Primary Tumors - Wu, Tianqi; Wan, Jian; Xia, Kai; Yang, Muqing; Feng, Lijin; Yin, Lu; Chen, Chunqiu (Frontiers in Oncology, 2022)
Clinically rare, multiple primary tumors are a growth or development of two or more neoplasms in the same individual. A 57-year-old woman with two primary cancers, namely, breast and gastric cancers, and a gastrointestinal stromal tumor was admitted. Next-generation sequencing (NGS) of the three tumors and blood was performed to determine their clonal origin and identify genetic cancer susceptibility. NGS identified that germline genetic variants potentially correlated with an individual risk of developing multiple cancers and that additional mutations are required to drive the formation of different tumors.